Sosialisasi Pembentukan Unit Penjaga Pantai untuk Menjaga Kebersihan Pesisir Pantai Budi Sun Resort - Rosalina Andriyani Ebang Pareira; Paulus Nong Wisang; Romualdus Paulus Sogen (Lembaga Pengembangan Kinerja Dosen, 2025)
The beach is an ecosystem that has an important role in human life, both as a natural resource, tourist attraction, and habitat for various marine biota. However, in reality, beach cleanliness currently does not receive special attention, so there is still rubbish in the beach environment, which often disturbs the beauty of the beach at Budi Sun Resort. This causes damage to the coastal environment and many coastal ecosystems even become extinct. This community service has three objectives, namely, 1) making participants aware of the importance of keeping the beach environment clean as a step to save the coastal ecosystem, and 2) forming a beach guard unit 3) cleaning the beach environment with the participants. This service method has two stages, namely the preparation stage and the implementation stage. The result of this service is the formation of a beach guard unit to maintain the cleanliness of the beach environment as a step to save the coastal ecosystem. Apart from that, it was proven that participants were enthusiastic when taking part in real activities and actions to clean the beach environment. However, assistance is still needed to recycle waste. This community service activity went according to plan and smoothly